(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article presents information on the relationship between public policy and the healthcare sector in the country, as well as its strategic work in healthcare. It also demonstrates that the country’s socioeconomic development plays a vital role in maintaining public health and developing the healthcare sector. It was emphasized that the medical sector, as one of the state’s key sectors, is obligated to provide high-quality and accessible services to the population. Therefore, public policy must fully support significant reforms and modernization of the healthcare system. Otherwise, improving the country’s population’s health and developing accessible medical care will pose serious challenges. Cooperation between the healthcare system and the government is crucial to overcoming a number of challenges. The author emphasizes that, in the context of a serious, acute epidemic, not all healthcare sectors can cope on their own. For example, it can be added that we overcame the COVID-19 epidemic in Kyrgyzstan not only thanks to the strength of the healthcare sector but also with the help of national, regional, district, and local authorities.